Partisipasi Masyarakat Dalam Program Bank Sampah: Model Logit - Ratiabriani, Ni Made; Purbadharmaja, Ida Bagus Putu (Jurnal Ekonomi Kuantitatif Terapan; 2016: Vol. 9, No. 1, Februari 2016 (pp. 1 - 88), 2016)
Increase of population, changes in consumption patterns and lifestyles of people in Denpasar certainly can increase the amount of landfill waste, types of waste, and the diversity of characteristics other debris. Bank of waste is a form of waste management based environment that serves as a sorting and collection of non-organic waste that can be recycled or reused to produce economic value. The aim of this study was to analyze how the people in the program participation waste bank in Denpasar and to analyze the influence of variables education level, household income, employment status, and number of family members significantly affect the chances of participation in the program garbage bank in Denpasar. Partisiapasi community in garbage bank program is the dependent variable is a dummy. This study uses primary data types, data was collected through interviews, questionnaires, and observations. The data analysis technique used is logit model. Based on the analysis found that people who actively participate in the program garbage bank in Denpasar that is equal to 64.3 percent. Education level, household income, employment status, and number of family members and significant positive effect on the chances of participation in the program garbage bank.
Keywords: public participation; waste bank; socio-economic conditions